The Digital Transformation Of Educational Administration: Innovation Strategies to Improve Educational Administration Services - Nasrullah Nasrullah (Al-Abshar: Journal of Islamic Education Management, 2025)
This study is grounded in the problem of low effectiveness in educational administration due to limited innovation, inadequate use of technology, and various barriers in managing educational services. The purpose of this study is to identify innovative strategic steps that can be implemented to improve the effectiveness of educational administration and to overcome existing challenges. This research employed a literature review method by examining various written sources such as books, journals, and scientific articles to build a theoretical foundation, strengthen arguments, and identify gaps in previous studies. The findings reveal that digital transformation is a key strategy, beginning with a situational and needs analysis to assess the digital readiness of educational institutions, including infrastructure, educators’ competencies, and learning patterns. Furthermore, measurable strategic objectives are established, such as improving access to digital education, enhancing the digital competencies of educators and staff, developing data-driven and student-centered learning systems, and implementing technology-based educational governance. These strategies are formulated into an action plan that includes program priorities, success indicators, resource allocation, and monitoring and evaluation mechanisms. The study contributes to the development of innovative, adaptive, and sustainable educational administration systems that support a more inclusive and globally competitive learning environment.